Circulating levels of insulin-like growth factor-II/mannose-6-phosphate receptor in obesity and type 2 diabetes - Jeyaratnaganthan, Nilani; Højlund, Kurt; Kroustrup, Jens Peter; Larsen, Jens Fromholt; Bjerre, Mette; Levin, Klavs; Beck-Nielsen, Henning; Frago, Susana; Hassan, A. Bassim; Flyvbjerg, Allan; Frystyk, Jan (Growth hormone & IGF research, 2010)
Abstract Objective The extracellular domain of the insulin-like growth factor II/mannose-6-phosphate receptor (IGF-II/M6P-R) is present in the circulation, but its relationship with plasma IGF-II is largely unknown. As IGF-II appears to be nutritionally regulated, we studied the impact of obesity, type 2 diabetes (T2D) and weight loss on circulating levels of IGF-II and its soluble receptor. Methods Twenty-three morbidly obese non-diabetic subjects were studied before and after gastric banding (GB), reducing their BMI from 59.3 ± 1.8 to 52.7 ± 1.6 kg/m2 . Lean controls ( n = 10, BMI 24.2 ± 0.5 kg/m2 ), moderately obese controls ( n = 21, BMI 31.8 ± 1.0 kg/m2 ) and obese T2D patients ( n = 20, BMI 32.3 ± 0.8 kg/m2 ) were studied before and after a hyperinsulinaemic euglycaemic clamp. Results Morbidly obese subjects had elevated IGF-II/M6P-R and IGF-II levels, which both decreased following GB (IGF-II/M6P-R: from 0.97 ± 0.038 to 0.87 ± 0.030 nmol/l, P = 0.001; IGF-II: from 134 ± 7 to 125 ± 6 nmol/l, P = 0.01), as did fasting plasma glucose and insulin ( P < 0.05). However, the metabolic parameters correlated with neither IGF-II nor IGF-II/M6P-R. Obese diabetics had increased IGF-II/M6P-R as compared with lean and obese controls (0.82 ± 0.031 vs. 0.70 ± 0.033 vs. 0.74 ± 0.026 nmol/l; P < 0.03) and levels were unaffected by clamp. In the latter cohort, IGF-II/M6P-R but not IGF-II correlated with HbA1c, and fasting plasma C-peptide, insulin and glucose (0.34 < r < 0.45; P < 0.05). In all subjects, BMI correlated with IGF-II/M6P-R ( r = 0.57; P < 0.001) and IGF-II ( r = 0.39; P < 0.005). IGF-II/M6P-R and IGF-II were not associated. Conclusion Serum IGF-II/M6P-R is up-regulated in morbid obesity, down-regulated by weight loss and elevated in moderately obese T2D. However, although plasma IGF-II was also reduced following GB, the two peptides were not statistically correlated. No acute effect of insulin was seen. These findings indicate that the IGF-II/M6P-R is nutritionally regulated, independently of IGF-II.